Prevalence, Severity, and Correlates of Anaemia in Pregnancy among Antenatal Attendees in Warri, South-Southern Nigeria: A Cross-Sectional and Hospital-Based Study - Victor Omote; Henry Awele Ukwamedua; Nathaniel Bini; Emmanuel Kashibu; Joel Rimamnde Ubandoma; Akafa Ranyang (Anemia)
Introduction. Anaemia in pregnancy affects about half of all pregnant women globally and constitutes an important reproductive health issue. The World Health Organization estimates that the prevalence of anaemia in pregnancy varies from 53.8% to 90.2% in developing countries and 8.3% to 23% in developed countries. Anaemia in pregnancy is common in developing countries and prevalence statistics required for its effective management and control is not adequately available in Nigeria. Thus, this study seeks to provide prevalence statistics of anaemia in pregnancy for the study region and its severity and highlight some possible correlates. Methods. A total of 218 pregnant women were recruited from the antenatal clinic of Central Hospital Warri using simple random technique after approval from the institutional review board and consent from the participants. Data on sociodemographics, economic status, and clinical history were collected using a pretested structured interviewer’s questionnaire. Participant’s haematocrit levels were estimated using standard laboratory techniques and anaemia was diagnosed using WHO-recommended cutoff. Results. The overall prevalence of anaemia was 37.6%. This prevalence dropped to 10.6% when a cutoff of less than 30% haematocrit was used. There was a direct relationship between haematocrit values and the participants’ age while mild anaemia accounted for the bulk (72%) of the anaemic cases. Participants younger than 20 years of age gave the highest age-based prevalence while parity-based prevalence was even among subgroups. Participants without formal education and those who were unemployed accounted for the highest prevalence in their different categories. Conclusion. Based on the findings from our study, anaemia in pregnancy is still of primary public health concern if WHO cutoff is used for the diagnosis. However, the reduction observed when less than 30% haematocrit was used tags our study zone to be of moderate severity. Although all variables lacked statistical significance, younger age, no formal education, and unemployment were highlighted to be predisposing factors.